2008
DOI: 10.1093/humrep/den486
|View full text |Cite
|
Sign up to set email alerts
|

Infertility patients' beliefs about their embryos and their disposition preferences

Abstract: Patients' conceptualization of their embryos plays an important role in embryo disposition decisions. Our research showed that patients deal with these decisions in a two-stage decision sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 21 publications
6
69
0
3
Order By: Relevance
“…A high receptivity to scientific and technological progress and trust in medical institutions and their professionals characterizes would-be-parents' assessment of the benefits and risks of assisted reproduction techniques, which was described in previous studies as being imbued with hope, trust and altruism (Silva and Machado, 2009. The reported reasons for donating embryos in this study reflect the incorporation of this assessment and are aligned with findings from other studies: willingness to contribute to scientific progress in general (Fuscaldo et al, 2007;Lyerly et al, 2006), to the development of IVF treatments in particular (Lyerly and Faden, 2007;Provoost et al, 2010) and to the improvement of human health (Fuscaldo et al, 2007;Provoost et al, 2009). These motives may also reflect the perception that minimal risks are associated with human embryo research, as mentioned by Priest et al (2003), which conflicts with the report of fears by patients who were unwilling to donate embryos for research.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A high receptivity to scientific and technological progress and trust in medical institutions and their professionals characterizes would-be-parents' assessment of the benefits and risks of assisted reproduction techniques, which was described in previous studies as being imbued with hope, trust and altruism (Silva and Machado, 2009. The reported reasons for donating embryos in this study reflect the incorporation of this assessment and are aligned with findings from other studies: willingness to contribute to scientific progress in general (Fuscaldo et al, 2007;Lyerly et al, 2006), to the development of IVF treatments in particular (Lyerly and Faden, 2007;Provoost et al, 2010) and to the improvement of human health (Fuscaldo et al, 2007;Provoost et al, 2009). These motives may also reflect the perception that minimal risks are associated with human embryo research, as mentioned by Priest et al (2003), which conflicts with the report of fears by patients who were unwilling to donate embryos for research.…”
Section: Discussionsupporting
confidence: 83%
“…This framework is useful in understanding why the Catholic men in our study were significantly more willing to donate embryos for research. Previous studies about the role of religion in IVF patients' decision about embryo disposition reported inconsistent data; studies in Australia (McMahon et al, 2003) and in Belgium (Provoost et al, 2009(Provoost et al, , 2010 found no association between an individual's religion and the disposition decision, although other studies in Switzerland (Mohler-Kuo et al, 2009) and Australia (Burton and Sanders, 2004) suggested that having moderate or strong religious beliefs (versus not very strong beliefs) was associated with a lower likelihood of donating embryos for research. In a qualitative study in the USA (Lyerly et al, 2006), pa- tients noted that religion affected their decision-making and identified themselves as Catholic (Evangelical) Christian, or Baptist, stating that they considered embryo destruction, including research, to be prohibited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disposition decisions were affected more by personal values, such as feelings about what family means, than by the ethical question of the 'rights' of the embryo. Qualitative interviews of Belgian IVF patients support this view (Provoost et al, 2009), where the most significant finding was that participants who perceived the embryo as being highly symbolic of the relationship between the couple were very reluctant to donate their cryopreserved embryos to others. Conceptualising the embryo in this way is more likely to occur when the embryo has been created from the couples' own gametes than when donor eggs or sperm have been used, or the embryo has already been donated from another couple.…”
Section: Donation and The Disposition Decisionmentioning
confidence: 94%